A three-year longitudinal study comparing bone mass, density, and geometry measured by dxa, pqct, and bone turnover markers in children with pku taking l-amino acid or glycomacropeptide protein substitutes - Daly, Anne (2021)
Funding Information: Funding: This research was funded by Vitaflo International as part of Ph.D. grant. Funding Information: Conflicts of Interest: A.D. research funding from Vitaflo International, financial support from Nutri-cia, Mevalia & Vitaflo International to attend study days & conferences. S.E. research funding from Nutricia, financial support from Nutricia & Vitaflo International to attend study days & conferences. A.P. has received an educational grant from Cambrooke Therapeutics and grants from Vitaflo International, Nutricia, Merck Serono, Biomarin and Mevalia to attend scientific meetings. C.A. received honoraria from Nutricia and Vitaflo International to attend study days and conferences. J.C.R. member of the European Nutritionist Expert Panel (Biomarin), the Advisory Board for Applied Pharma Research and Nutricia, and received honoraria as a speaker from APR, Merck Serono, Biomarin, Nutricia, Vitaflo, Cambrooke, PIAM and Lifediet. A.M. research funding & honoraria from Nutricia, Vitaflo International & Merck Serono, Member of European Nutrition Expert Panel (Merck Serono international), member of Sapropterin Advisory Board (Merck Serono international), member of the Advisory Board Element (Danone-Nutricia). The funders had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript, or in the decision to publish the results. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Copyright: Copyright 2021 Elsevier B.V., All rights reserved.